Turnaround Time And Radiology Workflow On The Effectiveness Of Hospital Services: A Systematic Literature Review - Rachella Christy Christy; Helena Andriani (Universitas Tribhuwana Tunggadewi, 2026)
Radiology turnaround time (TAT) is a crucial indicator of hospital service effectiveness, as delays in reporting can hinder clinical decisions, prolong queues, and disrupt patient flow. This systematic review examined how radiology workflows are measured, where bottlenecks occur, and which interventions improve TAT. The review followed PRISMA 2020 and searched PubMed, Scopus, Web of Science, Google Scholar, and Cochrane Library for hospital-based studies published from January 2019 to February 2026. Eligible studies reported TAT indicators, workflow stages, bottlenecks, or process-improvement interventions. Eighteen studies were included and synthesized narratively because TAT definitions and outcome measures were heterogeneous. Most studies measured TAT from image acquisition completion to preliminary, final, or signed reports, but several also used order-to-start, completion-to-PACS, time-to-view, and critical-result communication indicators. The main delays occurred during scheduling/preparation, image transfer, interpretation, reporting, and final communication. Lean redesign, protected emergency workflows, worklist optimization, dedicated emergency radiologists, 24/7 coverage, dashboard monitoring, and well-governed digital or AI tools reduced TAT and improved patient flow, including emergency department length of stay and time to surgery. Indonesian evidence remains limited and needs phase-based TAT standards, routine timestamp audits, and multi-site evaluation. Hospitals should prioritize standardized measurement before expanding technology-based interventions.